Impact of vegetarian and non-vegetarian diets on glycaemic control in type 2 diabetes mellitus patients: a cross-sectional study - Purohit, Pritam P.; Kumar, Ravi; Durgaraju, Susanth; Dawra, Saurabh; Duche, Suraj Gautam; Ashta, Kuldeep K. (International Journal of Research in Medical Sciences, 2025)
Background: Effective management of type 2 diabetes mellitus (T2DM) requires lifestyle modification alongside pharmacological therapy. Although vegetarian diets have been associated with a lower diabetes burden in Western populations, evidence regarding their effect on glycemic control among Indian patients with T2DM is limited. This study evaluated the association between dietary pattern (vegetarian versus non-vegetarian) and glycemic control in T2DM patients receiving oral hypoglycemic agents (OHAs). Methods: This cross-sectional study was conducted at a secondary care hospital in Alwar. 200 adults with T2DM were included (115 vegetarians, 85 non-vegetarians). Dietary classification was based on self-reported intake over the preceding 12 months. Fasting blood sugar (FBS), post-prandial blood sugar (PPBS), and glycated hemoglobin (HbA1c) were measured. Baseline demographics, body mass index (BMI), and medication adherence were recorded. Multivariate regression analysis was performed to assess independent association between diet and glycemic control after adjusting for confounders. Results: Vegetarian patients had significantly lower mean FBS (137.11±25.35 mg/dl versus 161.75±33.93 mg/dl), PPBS (180.24±34.07 mg/dl versus 241.15±52.55 mg/dl), and HbA1c levels (7.47±0.71% versus 8.72±1.42%) compared to non-vegetarians (p<0.001 for all). BMI was comparable between groups (p=0.089). Multivariate analysis showed a vegetarian diet to be independently associated with better glycemic control (OR=2.31; 95% CI: 1.48–3.62; p<0.001). Medication adherence also significantly influenced HbA1c (p=0.012). Conclusion: Vegetarian diet was associated with improved glycemic control in patients with T2DM, independent of BMI. These findings support dietary modification as an important adjunct to medical therapy, although larger, region-specific studies are needed to guide definitive dietary recommendations.